Biomarkers of Prostatic Cancer: An Attempt to Categorize Patients into Prostatic Carcinoma, Benign Prostatic Hyperplasia, or Prostatitis Based on Serum Prostate Specific Antigen, Prostatic Acid Phosphatase, Calcium, and Phosphorus. (12th January 2017) - Sarwar, Shahana; Adil, Mohammed Abdul Majid; Nyamath, Parveen; Ishaq, Mohammed
Abstract : Prostatitis, BPH, and P.Ca are the most frequent pathologies of the prostate gland that are responsible for morbidity in men. Raised levels of PSA are seen in different pathological conditions involving the prostate. PAP levels are altered in inflammatory or infectious or abnormal growth of the prostate tissue. Serum calcium and phosphorus levels were also found to be altered in prostate cancer and BPH. The present study was carried out to study the levels of PSA, PAP, calcium, and phosphorus in serum of patients with Prostatitis, BPH, or P.Ca and also to evaluate the relationship between them. Males in the age group of 50–85 years with LUTS disease symptoms and with PSA levels more than 4 ng/mL were included. A total of 114 patients were analyzed including 30 controls. Prostatitis in 35.7% of cases, BPH in 35.7% of the cases, and P.Ca in 28.57% of the cases were observed. Thus, the nonmalignant cases constitute a majority. PSA, a marker specific for prostatic conditions, was significantly high in all the diseases compared to controls. A rise in serum PSA and PAP indicates prostatitis or, in combination with these two tests, decreased serum calcium shows advanced disease.